The structural, thermal, and magnetic properties of manganese silicon sulfide. - Church, Christopher J. (University of Ottawa (Canada), 1994)
$\rm Mn\sb2SiS\sb4$ is a synthetic Olivine in which we have discovered an exceptional temperature dependent magnetic behavior that may lead to interesting applications. A state of spontaneous magnetization was found to exist in this material, but only between 83 and 86.5 K. In order to explain this unusual magnetic phenomena, polycrystalline samples of $\rm Mn\sb2SiS\sb4$ were first prepared from the elements and studied by SQUID magnetometry in low fields, by X-ray and neutron diffraction, by electron spin resonance (ESR) and by specific heat calorimetry. This research, in which the author was a member of a team, is described. His specific contributions include among others; the debugging and extension of some of the computer programs used to analyze the neutron diffraction results, the interfacing of the Bruker ESR spectrometer to a IBM compatible computer and the development of the computer progams to acquire the resonance curves and analyze the line spectra, the analysis of the ESR results, the assembly of parts of an apparatus and the development of a procedure to measure the specific heat of small samples in the 77 to 150 K range as well as some preliminary measurements on a sample of $\rm Mn\sb2SiS\sb4.$ These contributions are emphasized in this thesis. (Abstract shortened by UMI.)
Keywords: Physics, Condensed Matter.